Assessment Of Knowledge and Awareness Regarding Rapid Home Pregnancy Test Kits Among Newly Married Women and Their Utilization of RCH Services - Saroshe Satish; Mehta S C; Dixit Sanjay (Medsci Publications, 2012)
Objective: To assess the level of awareness and knowledge attitude, and practices of rapid home pregnancy test kit among married women of age group 18-45 years with no history of previous pregnancy & study the utilization of RCH services including early ANC registration and Institutional delivery. Methods: Study subjects were identified using SRS then Interpersonal interview sessions were held about rapid pregnancy detection kit. The pregnancy outcomes of those women who used Rapid Pregnancy detection kit was followed till delivery and those women who underwent institutional delivery were identified. Results: 58.53% of the total women who used rapid home pregnancy test kit used Nishchaya kit, 71.9% had registered for the ANC in less than 20 weeks & 54.8% underwent institutional delivery. Conclusions: Urine based pregnancy detection kit is a definite method of early diagnosis of pregnancy which ultimately leads to early ANC registration & institutional delivery.